Sustaining faith - Oke, Janette, 1935-; Logan, Laurel Oke (When hope calls, 2021)
"With more children on their way from England who need caring homes, Lillian and Grace Walsh must use every ounce of gumption to keep their mission alive. But when startling information about the past surfaces and a new arrival comes via suspicious circumstances, they'll have to decided what is worth fighting for and what is better left in God's hands"--